2006
DOI: 10.1242/dev.02265
|View full text |Cite
|
Sign up to set email alerts
|

An ancient Wnt-Dickkopf antagonism inHydra

Abstract: The dickkopf (dkk) gene family encodes secreted antagonists of Wnt signalling proteins, which have important functions in the control of cell fate, proliferation, and cell polarity during development. Here, we report the isolation, from a regeneration-specific signal peptide screen, of a novel dickkopf gene from the fresh water cnidarian Hydra. Comparative sequence analysis demonstrates that the Wnt antagonistic subfamily Dkk1/Dkk2/Dkk4 and the non-modulating subfamily Dkk3 separated prior to the divergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
174
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(192 citation statements)
references
References 74 publications
14
174
2
2
Order By: Relevance
“…Taken together, these observations suggest a deep split into Dkk3 and Dkk1/2/4 gene families during early metazoan evolution, and more recent gene duplications accompanied by functional divergence of the two Dkk subfamilies (Guder et al, 2006).…”
Section: Evolution Of Dkk Genesmentioning
confidence: 69%
See 4 more Smart Citations
“…Taken together, these observations suggest a deep split into Dkk3 and Dkk1/2/4 gene families during early metazoan evolution, and more recent gene duplications accompanied by functional divergence of the two Dkk subfamilies (Guder et al, 2006).…”
Section: Evolution Of Dkk Genesmentioning
confidence: 69%
“…In some invertebrate Dkks such as the Hydra ortholog Hydkk1/2/4, only the colipase fold occurs (Guder et al, 2006) and structurefunction analysis of vertebrate Dkks has shown that this domain alone is sufficient for biological activity, that is, Wnt inhibition (Brott and Sokol, 2002;Li et al, 2002;Mao and Niehrs, 2003). The colipase fold also shows the greatest sequence conservation among the Dkks.…”
Section: Physical Properties and Structure Of Dkk Proteinsmentioning
confidence: 99%
See 3 more Smart Citations